Peran Bauran Pemasaran dan Kelompok Acuan terhadap Keputusan Memilih Laboratorium Rumah Sakit AL Huda Genteng Banyuwangi - Priyanto, Soegeng Hery; Hariyanti, Tita; ., Fatchurohmani (Universitas Brawijaya, Indonesia, 2012)
To analyze the marketing mix factors and the reference/reference that affect patients to conductexaminations in the Al Huda laboratory simultaneously and or partially. Identify the problems contained inthe marketing mix at Al Huda Hospital's Laboratory.This on coming research uses a quantitative approach.Analytic descriptive study design with Cross Sectional Study approach. A total of 80 patients were respondentsin this study, they fill out a questionnaire that has been provided. Then statistical analysis wasperformed using multiple linear regression analysis. Results showed that simultaneously (together) themarketing mix variables and reference group have influence on selecting the decision variables (Fcountof0.000<0.05). Partially, price variable (tcountof0.048) and employees (tcount0.013) are the ones that influencethe decision of selecting the Al Huda laboratory as examination place, while other variables did not.